Effect of the application of pyraclostrobin in the initial growth of arabic coffee in different availability of water - Peloso, Anelisa Figueiredo; Tatagiba, Sandro Dan; Amaral, José Francisco Teixeira; Cavatte, Paulo Cesar; Tomaz, Marcelo Antônio (Coffee Science - ISSN 1984-3909, 2017)
The objective of this research was to investigate the effect of pyraclostrobin on the initial growth of Coffea arabica L. plants submitted or not to water deficit, using the total dry matter (MST), aerial part matter (MSPA), root matter (MSR), foliar area (AF), height and diameter, further on of the efficiency in the use of yield water (EUAp) in plants grown at 100 (-DH, without water deficit) and 30% (+DH, with water deficit) of available water in the substrate. According to the results, it was verified that the application of pyraclostrobin in plants submitted to -DH, mainly in the highest concentration (1.4 g/L), favored the increase of MST, MSPA, MSR, leaf area, height, diameter and EUAp. Under water deficit (+DH), plant growth was not favored by the application of pyraclostrobin, independently of the concentration used, evidencing the need for adequate water control as a management strategy for production.